The comparison of conventional and digital photography as a medium of crime scene investigation / Nadzri Hj Mohd Sharif, Datuk Prof Madya Dr Mizan Hj Hitam and Shaharin Sulaiman - Mohd Sharif, Nadzri; Hitam, Mizan; Sulaiman, Shaharin (Research Management Institute (RMI), 2012)
The problem of this research is the use of new implementation of Digital camera in police investigation, where digital camera is different from the conventional camera. By using the digital camera, the heavy task of forensic photographer becomes simple. While many of them knew about the advantage of using the digital camera, most of them doesn't even know that the image from the digital camera can arose suspicion among administrative of justice (Prof Dr Akram 2010). They did not realize that the same issue which haunted the conventional method regarding the image authentication, will also happening the digital method. In this research, we analyzed the comparison of conventional and digital camera for the purpose to differentiate which of the images can enhance and smoothen the investigation works…